The antioxidant activity of a prenyl flavonoid alters its antifungal toxicity on Candida albicans biofilms - Peralta, Mariana Andrea (2018)
The antioxidant effect of 8PP, a prenylflavonoid from Dalea elegans on Candida albicans biofilms, was investigated. We previously reported that sensitive (SCa) and resistant C. albicans (RCa) biofilms were strongly inhibited by this compound, in a dose-depending manner (50 μM-100 μM), with a prooxidant effect leading to accumulation of endogenous oxidative metabolites and increased antioxidant defenses. In this work, the antifungal activity of high concentrations of 8PP (200–1000 μM), the cellular stress imbalance and the architecture of biofilms were evaluated. Biofilms were studied by crystal violet and confocal scanning laser microscopy (CSLM) with COMSTAT analysis. Superoxide anion radical, the activity of the superoxide dismutase and the total antioxidant capacity were measured. Intracellular ROS were detected by a DCFH-DA and visualized by CSLM; reactive nitrogen intermediates by Griess. An antioxidant effect was detected at 1000 μM and levels of oxidant metabolites remained low, with major changes in the SCa. COMSTAT analysis showed that biofilms treated with higher concentrations exhibited different diffusion distances with altered topographic surface architectures, voids, channels and pores that could change the flow inside the matrix of biofilms. We demonstrate for first time, a concentration-dependent antioxidant action of 8PP, which can alter its antifungal activity on biofilms.